EFEKTIVITAS SUPERVISI AKADEMIK BERBASIS COACHING DALAM MENINGKATKAN PROFESIONALISME GURU DI SMP 1 REMBANG - Nuraini; Ummil Makarim Fibrianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The quality of education in Indonesia is still an issue that requires serious attention. One of the main determining factors for the quality of education is teacher professionalism. Professional teachers are able to carry out their strategic role in designing, implementing and evaluating the learning process effectively. Academic supervision implemented by school principals is certainly very effective, because it can provide assistance, guidance and guidance to teachers so that they are able to work better in guiding students and can improve the quality of learning in improving learning in schools. The aim of the research is to determine the effectiveness of implementing coaching-based academic supervision in increasing teacher professionalism. This research uses a qualitative approach. Data collection techniques are carried out through interviews, observation and documentation. The research subjects were principals, supervisors and teachers at SMP Negeri 1 Rembang. The research results found that the supporting factors for the implementation of school principal academic supervision include: principal, teachers,. The principal has high concern for teachers to improve their teaching abilities, so that teachers are able to excel, and teachers have high awareness and motivation to improve their teaching abilities. In implementing academic supervision by the principal, it can be carried out in three stages, namely: conducting pre-academic supervision, carrying out class visits, and discussing the results of class visits. The implementation of an effective academic supervision program means that to achieve the required quality, it requires serious supervision by the school principal. The implementation of academic supervision by the school principal towards teachers is very important in order to improve teachers' professional abilities and improve the quality of learning through a good learning process. The essence of academic supervision is not assessing teacher performance in managing the learning process, but rather helping teachers develop their professionalism.